2019
DOI: 10.1111/jpi.12553
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin modulates daytime‐dependent synaptic plasticity and learning efficiency

Abstract: Mechanisms of hippocampus‐related memory formation are time‐of‐day‐dependent. While the circadian system and clock genes are related to timing of hippocampal mnemonic processes (acquisition, consolidation, and retrieval of long‐term memory [LTM]) and long‐term potentiation (LTP), little is known about temporal gating mechanisms. Here, the role of the neurohormone melatonin as a circadian time cue for hippocampal signaling and memory formation was investigated in C3H/He wildtype (WT) and melatonin receptor‐knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 83 publications
(242 reference statements)
1
39
0
Order By: Relevance
“…Immunohistochemical analysis showed that MT1 and MT2 expression patterns partially overlap, with MT1 being expressed predominantly in the CA1 hippocampal subfield and MT2 in the CA3/CA4 subfields . Our present results allow unambiguous identification of MT2‐expressing cells in the hippocampus, and apparent absence of MT1, and should facilitate experimental studies on the mechanism of MLT action on memory …”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Immunohistochemical analysis showed that MT1 and MT2 expression patterns partially overlap, with MT1 being expressed predominantly in the CA1 hippocampal subfield and MT2 in the CA3/CA4 subfields . Our present results allow unambiguous identification of MT2‐expressing cells in the hippocampus, and apparent absence of MT1, and should facilitate experimental studies on the mechanism of MLT action on memory …”
Section: Discussionmentioning
confidence: 56%
“…44 Our present results allow unambiguous identification of MT2-expressing cells in the hippocampus, and apparent absence of MT1, and should facilitate experimental studies on the mechanism of MLT action on memory. [76][77][78][79][80][81] The moderate MLT receptor immunoreactivity in the rat dorsal raphe nucleus suggested the possible involvement of MT1 receptors in the pathogenesis of depression. 44 This is supported by a study which demonstrated behavioral changes mimicking the symptoms of melancholic depression in MLT receptor knockout mice.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, expression peak times correlate with the species' temporal niche . Melatonin can reset hippocampal clocks but pinealectomy does not markedly affect clock protein rhythmicity …”
Section: Brain Clocks Outside the Scnmentioning
confidence: 99%
“…Daily repeating phenomena, thus, coordinate widespread functions like temperature control [59][60][61], cardiovascular performance [62], autonomic [63], and endocrine regulations [49,64,65], as well as, behavior [52,53,66,67]. Biological oscillators, thus, effectively contribute to sustain homeostasis [30,68] and related functions like preconditioning (hormesis) and learning [69][70][71][72][73][74]. Even everyday coupling of rhythms between subjects has a neurophysiological substrate [75].…”
Section: Rhythms An Information Systemmentioning
confidence: 99%